2007
DOI: 10.1021/es070288t
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure of Juvenile Rainbow Trout (Oncorhynchus mykiss) to 1,2-bis(2,4,6-tribromo- phenoxy)ethane:  Bioaccumulation Parameters, Biochemical Effects, and Metabolism

Abstract: Juvenile rainbow trout (Oncorhynchus mykiss) were exposed in the laboratory to an environmentally relevant dose of 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE) via their diet for 49 days, followed by 154 days of untreated food to examine bioaccumulation parameters, potential biochemical effects, and metabolic products. There was a linear increase in the amount of BTBPE in fish during the uptake phase of the experiment, and an uptake rate constant of 0.0069 +/- 0.0012 (arithmetic mean +/- 1 x standard error) nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…BMFs for walleye ranged from 0.4 to 2.5 depending on the prey. The propensity of BTBPE to biomagnify was confirmed in a laboratory feeding study in juvenile rainbow trout (Oncorhynchus mykiss) [31]. BTBPE was taken up from the gut with an assimilation efficiency of 27% over the 49 day feeding period, resulting in a BMF of 2.3.…”
Section: Invertebrates and Fishmentioning
confidence: 84%
“…BMFs for walleye ranged from 0.4 to 2.5 depending on the prey. The propensity of BTBPE to biomagnify was confirmed in a laboratory feeding study in juvenile rainbow trout (Oncorhynchus mykiss) [31]. BTBPE was taken up from the gut with an assimilation efficiency of 27% over the 49 day feeding period, resulting in a BMF of 2.3.…”
Section: Invertebrates and Fishmentioning
confidence: 84%
“…Decreases in total T4 and induction of T4-glucuronosyl transferase seem to suggest that HBCD may act in a similar manner to that of the PBDEs, likely through interaction with PXR (Fery et al, 2009;van der Ven et al, 2006). On the contrary, BTBPE was shown not to act on the thyroid system in rainbow trout (Oncorhynchus mykiss) (Tomy et al, 2007), although it does exert thyroid-disrupting effects in chicken embryonic hepatocytes (Egloff et al, 2011). Additional toxicity studies are required to rule out or confirm the disruptive ability of these compounds and other brominated flame retardants still poorly studied.…”
Section: Alternative Flame Retardantsmentioning
confidence: 94%
“…per day) for 49 days, resulted in an average concentration in muscle of about 0.3 µg/kg (Tomy et al, 2007). The uptake curve suggested that BTBPE did not reach steady state in fish at the end of the exposure period.…”
Section: Hazard Identificationmentioning
confidence: 99%